Evaluation Of The Role Of CT Scan In The Investigation Of Lymph Node Enlargement In Cervical Cancer Patients - محمد, محمد; الزيات , مروان (Latakia University Journal -Medical Sciences Series, 2024)
Objective: to assess the sensitivity and quality of preoperative CTscan in determining the presence of enlarged lymph nodes in patients with cervical cancer. Methods: the study included data of 43 patientsdiagnosed with cervical cancer, CTscan was performed before surgery for all patients after histologically determining the type of cancer. Results: the age of the patients ranged from28-75 years, the majority of them were smokers and multiple birth , squamous cell cancer was the most common histological type in the affected women. The sensitivity, specificity, and both the positive and negative predictive value of CTscan were high. Conclusion: preoperative CT scan is an accurate diagnostic method for determining the presence of enlarged lymph nodes in cervical cancer patients, especially in poor countries and resource-limited communities, which helps in choosing the right treatment.